2017
DOI: 10.1007/s10856-017-6011-7
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of metallosis associated with spine instrumentation

Abstract: The characteristic trait of metallosis is the presence of tissue staining. Analyzing explanted revision hardware from spine surgeries and performing ICPMS/AES analysis on removed tissue samples, a clinically relevant definition for metallosis may be developed. Results of the analysis identified hardware fretting wear and corrosion, and ICP-MS/AES analysis identified elevated metal ion concentrations in all cases. This supports the hypothesis that corrosion may be linked to poor health outcomes and potential ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Elevated concentrations of trace metals (Al, Co, Cr, Ni, Mo, and Ti) have been reported in the whole blood of patients with failed metallic spinal implants [28,38], in plasma [52] and serum [10,22,23,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][53][54][55][57][58][59][60][61][63][64][65][66], urine [23,55], and in soft tissue [9,27,28,30,31]. Several studies reported in the literature describe the determination of metals in patients with spinal implants by spectrometric techniques, among them inductively coupled plasma mass spectrometry (ICP-MS) [9,22,28,[37][38][39][40][41]…”
Section: Clinical Reactions To Spinal Implant Debrismentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated concentrations of trace metals (Al, Co, Cr, Ni, Mo, and Ti) have been reported in the whole blood of patients with failed metallic spinal implants [28,38], in plasma [52] and serum [10,22,23,37,[39][40][41][42][43][44][45][46][47][48][49][50][51][53][54][55][57][58][59][60][61][63][64][65][66], urine [23,55], and in soft tissue [9,27,28,30,31]. Several studies reported in the literature describe the determination of metals in patients with spinal implants by spectrometric techniques, among them inductively coupled plasma mass spectrometry (ICP-MS) [9,22,28,[37][38][39][40][41]…”
Section: Clinical Reactions To Spinal Implant Debrismentioning
confidence: 99%
“…Hypotheses generated from the arthroplasty studies including remain inconclusive when applied in spine as the devices and the tissues are not similar. At this point a literature search has uncovered only a very few reported spinal metallosis cases [6][7][8][9][10][11]. Goldenberg et al [6] found only three relevant articles regarding spinal metallosis (excluding all arthroplasty related studies).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major challenges for them is to sustain their bio-compatibility, bio-safety and bio-functionality in the human body having certain magnitude of pH value. A team investigators during their research perceived that employed artificial-implants such as hip-replacement, dental implants, screws to hold them, spinal implants, and many more failed, owing to corrosion and in vivo-galling [158][159][160][161][162][163][164][165][166][167]. The anti-galling characteristic of the sliding surface can be improved by various means as discussed in the previous sections out of which the application of the fluoro-based functional coating is the most suitable method that was adopted to counter the issue friction, wear and in vivo-galling [168][169][170][171].…”
Section: Limitation Of Fluoro-based Polymersmentioning
confidence: 99%
“…Metallosis is a rare and poorly understood phenomenon in the surgical literature. Metallosis is defined as the deposition of metal ions in tissue [1] , [2] , [3] , [4] . It may trigger an inflammatory response, which can result in various types of metal induced pathologies.…”
Section: Introductionmentioning
confidence: 99%